2020
DOI: 10.1111/1759-7714.13338
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis and treatment of immune checkpoint inhibitor‐associated adverse events in the digestive system

Abstract: Immunotherapy for malignant tumors is a hot spot in current research and the treatment of cancer. The activation of programmed cell death receptor‐1 (PD‐1) and cytotoxic T lymphocyte‐associated antigen 4 (CTLA)‐4 relevant signaling pathway can inhibit the activation of T lymphocytes. Tumor cells can achieve immune escape by activating this signaling pathway. By inhibiting this signaling pathway, immune‐checkpoint inhibitors (ICIs) activate T lymphocytes to clear the tumor cells. Therefore, the adverse effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…[7][8] However, immunotherapies still have limitations in clinical application such as pseudoprogression, hyperprogression, primary or adaptive drug resistance, and side effects. [9][10][11][12][13] Therefore, it is important to find new immunotherapy targets to improve the efficacy of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8] However, immunotherapies still have limitations in clinical application such as pseudoprogression, hyperprogression, primary or adaptive drug resistance, and side effects. [9][10][11][12][13] Therefore, it is important to find new immunotherapy targets to improve the efficacy of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The primary symptoms of immune checkpoint inhibitor-induced colitis (ICIIC) include watery stool and non-bloody diarrhea, with abdominal pain, blood in the stool, nausea, vomiting, weight loss, and fever ( 1 ). Studies indicate that patients in the αCTLA-4 group have a higher incidence of GI-irAEs and more frequent diarrhea than patients in the αPD-1/PD-L1 group.…”
Section: Status Quo Of Iciicmentioning
confidence: 99%
“…In recent years, the global cancer incidence has been steadily rising. Traditional cancer treatments include surgery, radiotherapy, chemotherapy, targeted therapy, and interventional therapy ( 1 ). Immunotherapy has become the fifth pillar of cancer management alongside surgery, chemotherapy, radiotherapy, and targeted therapy ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous studies reported that 9% of 131 evaluable patients were considered to have HP (defined as a twofold increase in the tumor growth rate between the reference and experimental periods) [17]. In addition, patients treated with nivolumab (a humanized mAb against PD-1) were found to be at a higher risk of developing side effects, such as interstitial pneumonia and colitis [21][22][23][24][25]. Most importantly, it has been confirmed that only 20% of patients benefit from immune checkpoint blockade therapy in clinical studies [26], with the rest of the patients showing primary or adaptive drug resistance to varying degrees [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%